Chatbot Use foradmissions - N.Guntupalli Manojkumar,Mr. S. Niresh Kumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The communication of potential students with a university department is performed manually and it is a very time-consuming procedure. The opportunity to communicate with on a oneto- one basis is highly valued. However, with many hundreds of applications eachyear, one-to-one conversations are not feasible in most cases. The communication will require a member of academic staff toexpend several hours to find suitable answers and contact each student. It would be useful to reducehis costsand time. The project aims to reduce the burden on the head of admissions, and potentially other users, bydeveloping a convincing chat bot. A suitable algorithm must be devised to search through the set ofdata and find a potential answer. The program then replies to the user and provides a relevant weblink if the user is not satisfied by the answer. Furthermore, a web interface is provided for both usersandan administrator. The achievements of the project can be summarized as follows. To prepare the background of theproject a literature review was undertaken, together with an investigation of existing tools, andconsultation with the head of admissions. The requirements of the system were established and arange of algorithms and tools were investigated, including keyword and template matching. Analgorithm that combines keyword matching with string similarity has been developed. A usablesystem using the proposed algorithm has been implemented.The system was evaluated by keepinglogsof questions andanswers and byfeedback received bypotentialstudents that used it.